The Effect of Digital Literacy and the Use of Educational Social Media on Economics Learning Motivation of Grade XI Students at State Senior High School 11 Jambi City - Hasnatang Hasnatang; Fadilla Ulfah; Arpizal Arpizal (International Journal Education and Computer Studies (IJECS), 2026)
This study aims to analyze the influence of digital literacy and the use of educational social media on students’ learning motivation at SMP Negeri 3 Kendari. The research employed a quantitative approach using a survey method. The population consisted of all students, with the sample determined using a proportional sampling technique. Data were collected through questionnaires and analyzed using multiple linear regression. The results show that digital literacy has a positive and significant effect on students’ learning motivation. Meanwhile, the use of educational social media has a positive but not statistically significant effect on learning motivation. Simultaneously, digital literacy and the use of educational social media have a significant effect on students’ learning motivation, with a coefficient of determination (R²) of 0.256, indicating that 25.6% of the variation in learning motivation is explained by both variables. These findings suggest that improving students’ digital literacy is essential in enhancing their learning motivation. Although the use of educational social media contributes positively, its role is not yet optimal and requires more effective integration into the learning process.